Hard x-ray photoelectron spectroscopy: a snapshot of the state-of-the-art in 2020. (13th May 2021) - Kalha, Curran; Fernando, Nathalie K; Bhatt, Prajna; Johansson, Fredrik O L; Lindblad, Andreas; Rensmo, Håkan; Medina, León Zendejas; Lindblad, Rebecka; Siol, Sebastian; Jeurgens, Lars P H; Cancellieri, Claudia; Rossnagel, Kai; et al.
Abstract: Hard x-ray photoelectron spectroscopy (HAXPES) is establishing itself as an essential technique for the characterisation of materials. The number of specialised photoelectron spectroscopy techniques making use of hard x-rays is steadily increasing and ever more complex experimental designs enable truly transformative insights into the chemical, electronic, magnetic, and structural nature of materials. This paper begins with a short historic perspective of HAXPES and spans from developments in the early days of photoelectron spectroscopy to provide an understanding of the origin and initial development of the technique to state-of-the-art instrumentation and experimental capabilities. The main motivation for and focus of this paper is to provide a picture of the technique in 2020, including a detailed overview of available experimental systems worldwide and insights into a range of specific measurement modi and approaches. We also aim to provide a glimpse into the future of the technique including possible developments and opportunities.